2018
DOI: 10.1038/s41591-018-0042-6
|View full text |Cite
|
Sign up to set email alerts
|

Epitope-based vaccine design yields fusion peptide-directed antibodies that neutralize diverse strains of HIV-1

Abstract: A central goal of HIV-1 vaccine research is the elicitation of antibodies capable of neutralizing diverse primary isolates of HIV-1. Here we show that focusing the immune response to exposed N-terminal residues of the fusion peptide, a critical component of the viral entry machinery and the epitope of antibodies elicited by HIV-1 infection, through immunization with fusion peptide-coupled carriers and prefusion stabilized envelope trimers, induces cross-clade neutralizing responses. In mice, these immunogens e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
279
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 259 publications
(285 citation statements)
references
References 80 publications
5
279
0
1
Order By: Relevance
“…One approach to focus the response on the FP is through repeated immunization with 10-100s of copies of the FP displayed on carrier proteins, such as keyhole limpet hemacyanin (KLH), followed by a booster immunization with the Env trimer spike to present the FP in a more native context. This approach has produced encouraging responses in animals with up to 31% and 59% neutralization breadth in mice and macaques, respectively, against panel of diverse HIV isolates [27,28]**. This concept is now being developed for human clinical trials [29].…”
Section: Introductionmentioning
confidence: 99%
“…One approach to focus the response on the FP is through repeated immunization with 10-100s of copies of the FP displayed on carrier proteins, such as keyhole limpet hemacyanin (KLH), followed by a booster immunization with the Env trimer spike to present the FP in a more native context. This approach has produced encouraging responses in animals with up to 31% and 59% neutralization breadth in mice and macaques, respectively, against panel of diverse HIV isolates [27,28]**. This concept is now being developed for human clinical trials [29].…”
Section: Introductionmentioning
confidence: 99%
“…Clustering of the PCA results indicated that the F14 and F14/Vt8 structures indeed differed from the majority of the available SOSIP structures, residing in distinct clusters closer to a cluster of fusion peptide-directed antibody-bound SOSIP structures including those induced in mice and Rhesus macaques (Figure 5E, Supplementary Table 5). 38 This finding indicated that the changes observed in the layer1/2 contact region with gp41 indeed altered the overall orientation of gp120 relative to gp41, and showed that these changes were structurally similar to those induced by fusion peptide-directed antibodies. We next examined the structure of the vFP antibodies in the region of the F14 conformational changes.…”
Section: Resultsmentioning
confidence: 74%
“…They immunized guinea pigs and macaques with a fusion peptide coupled to the carrier protein KLH, and boosted the responses with stabilized BG505 SOSIP trimers. This immunization strategy induced autologous NAb responses in all the animals and substantial NAb responses against heterologous Tier-2 viruses in some animals [88]. When they isolated the antibodies that were responsible for the broad neutralization they could confirm that these antibodies targeted the fusion peptide on both autologous and heterologous viruses [88].…”
Section: Evaluating Env Trimers In Vivo: Learning From Different Immumentioning
confidence: 98%